High photocatalytic efficiency of inkjet printed patterns by formulation of eco-friendly TiO2-based inks - J. Yus; Z. Gonzalez; A.J. Sanchez-Herencia; A. Sangiorgi; A. Sanson; C. Galassi; B. Ferrari (Open Ceramics, 2021)
High photocatalytic performances of inkjet printed patterns has been achieved by a green formulation of water-based suspension including commercial TiO2 nanoparticles (NPs). The reaction rate constant (k > 3.79 × 10−3min−1cm-2) of the manufactured patterns presented competitive photoresponses in comparison with others complex formulations based on sol-gel process. Optimized conditions of the colloidal dispersion and stabilization of TiO 2 NPs using diethylene glycol as cosolvent, allowed a constant and homogeneous jetting flow, fitting the surface tension and viscosity values suitable for the piezo-driven technology selected. The nanostructure-based pattern printed with micro-resolution achieved the 90% methyl orange degradation after 9h of light exposition and the 100% after 13h in a stirred tank reactor. Moreover, the reusability of printed patterns has been also proved since they preserve their photocatalytic activity and microstructure after sequential tests.This new finding is expected to be particularly useful to industrial fabrication of microdesign and immobilized patters onto different substrates-types.